Konsep Metode Pendidikan Islam dalam Perspektif Tafsir Al-Qur’an Surah al-Nahl (16) Ayat 125 - Nur Zaskyah; Sulkifli; Abd. Hapid; Nurnanensi; Yulfi Nazila Putri; Junaidi (Al-Kindi, 2026)
This study analyzes the concept of Islamic educational methods according to the interpretation of QS. An-Nahl/16:125 and assesses its relevance to the modern educational context. The research method is a library research study with a thematic interpretation approach (maudhu'i), through the study of the verses of the Qur'an, books of interpretation, and scientific literature related to Islamic educational methods. The results show that QS. An-Nahl/16:125 contains three main approaches in Islamic education: hikmah, which emphasizes wisdom and a rational approach; mau'izhah hasanah, which prioritizes good advice and emotional touch; and mujadalah, which emphasizes polite and argumentative dialogue. These three approaches are in line with the principles of modern learning, including the development of critical thinking, character education, and active learning. Thus, the educational methods contained in the verse are relevant for implementation in the learning process to create an effective, humanistic learning atmosphere and focus on the development of students' potential as a whole